Risk factors for the presentation of bacteriuria in cats with lower urinary tract disease: a retrospective analysis of 102 cases (2008 – 2015) - Jordán D., Christian (2020)
The aim of this retrospective study was to describe the results of bacterial isolates and to determine the risk factors involved in the presentation of bacteriuria in cats with lower urinary tract disease (FLUTD). Clinical records of feline patients (n=102) who underwent urinalysis and urine culture were collected. The following variables were considered: age, sex, reproductive status, breed, bodyweight, season, colour of urine, urine odour, urine density, pH, glucose, proteins, blood, leukocytes, erythrocytes, crystals and type of crystals. In 60.8% (62/102) of the samples, bacteria were isolated in urine, including E. coli 40.3% (25/62), Klebsiella sp 12.9% (8/62), Staphylococcus sp 12.9% (8 / 62), Proteus sp 8.1% (5/62), Enterobacter sp 8.1% (5/62) and Staphylococcus epidermidis 6.4% (4/62). Age, urinary density and presence of blood were statistically significant. In addition, it was determined that the urine density, the red colour of the urine, the presence of leukocytes and crystals represent risk factors (p <0.05) for the occurrence of bacteriuria.